Penerapan E-Government Ditingkat Kabupaten (Case Study Kabupaten Pelalawan Riau) - Angraini . (Jurnal Sistem Informasi, 2015)
Abstract In the master plan guides the development of e-Government, e-government implementation aimed towards good governance, the concept of e-Government should be applied at every level of government agencies and regional centers. The central government will coordinate with local governments in developing and implementing e-government. One of the objectives of e-government is to assist in the process of both central and local government. To support the implementation of the tasks of the government and development and addressing society's demands for transparency, efficiency and better services by utilizing information technology, the Government Pelalawan sees the need of development in the field of Information Technology Development. Local government district. Pelalawan very aware of the importance of implementing e-government service delivery govermant in. In the application of e govermant adapted to the development of e-govermant roadmap made in accordance with the conditions and requirements of information technology. Keywords: e-government, governance, information, technology, regional     Abstrak Dalam panduan pengembangan master plan e-goverment, penerapan e-government bertujuan untuk menuju good governance maka konsep e-Government harus diterapkan di setiap lembaga pemerintah tingkat pusat dan daerah. Pemerintah pusat akan berkoordinasi dengan pemerintah daerah dalam mengembangkan dan menerapkan  e-government. Salah satu tujuan penerapan e-government adalah untuk membantu dalam proses pemerintahan baik pusat maupun daerah.  Untuk menunjang pelaksanaan tugas pemerintahan dan pembangunan serta menjawab tuntutan kebutuhan masyarakat akan keterbukaan, efisiensi dan pelayanan yang lebih baik dengan memanfaatkan teknologi informasi, maka Pemerintahan Kabupaten Pelalawan memandang perlu pembangunan di bidang Pengembangan Teknologi Informasi. Pemerintah daerah Kab. Pelalawan sangat menyadari pentingnya penerapan e- govermant dalam penyelenggaraan pelayanan pemerintahan. Dalam penerapan e- govermant disesuai dengan roadmap pengembangan e- goverment yang dibuat sesuai dengan kondisi teknologi informasi dan kebutuhan. Kata kunci: e- goverment, governance, teknologi, informasi, daerah